2019
DOI: 10.1016/j.molmet.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute β-adrenoceptor mediated glucose clearance in brown adipose tissue; a distinct pathway independent of functional insulin signaling

Abstract: Objectiveβ-adrenoceptor mediated activation of brown adipose tissue (BAT) has been associated with improvements in metabolic health in models of type 2 diabetes and obesity due to its unique ability to increase whole body energy expenditure, and rate of glucose and free fatty acid disposal. While the thermogenic arm of this phenomenon has been studied in great detail, the underlying mechanisms involved in β-adrenoceptor mediated glucose uptake in BAT are relatively understudied. As β-adrenoceptor agonist admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
(80 reference statements)
0
13
1
2
Order By: Relevance
“…The inhibitory effect of the β 3 -AR agonist CL 316243 observed in adipocytes from WT mice and reproduced to a lesser extent in rat adipocytes is in perfect agreement with previous reports on glucose transport inhibition in adipocytes by β-AR stimulation[ 31 , 51 , 53 , 54 ]. This also explains the slightly enhanced basal uptake found in the "β-less" mice, but contrasts with other previous studies claiming that CL 316243 stimulates glucose uptake in mouse brown adipocytes in culture[ 55 ] as well as β-AR activation under in-vivo conditions[ 42 ]. Indeed, such controversy does not appear to have great relevance for the regulation of glucose uptake in human adipocytes, the β 3 -adrenergic component of which is remarkably weak[ 56 ], and in which short-term CL 316243 administration neither induces alterations in the early insulin signalling cascade nor changes the basal level of glucose uptake[ 57 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The inhibitory effect of the β 3 -AR agonist CL 316243 observed in adipocytes from WT mice and reproduced to a lesser extent in rat adipocytes is in perfect agreement with previous reports on glucose transport inhibition in adipocytes by β-AR stimulation[ 31 , 51 , 53 , 54 ]. This also explains the slightly enhanced basal uptake found in the "β-less" mice, but contrasts with other previous studies claiming that CL 316243 stimulates glucose uptake in mouse brown adipocytes in culture[ 55 ] as well as β-AR activation under in-vivo conditions[ 42 ]. Indeed, such controversy does not appear to have great relevance for the regulation of glucose uptake in human adipocytes, the β 3 -adrenergic component of which is remarkably weak[ 56 ], and in which short-term CL 316243 administration neither induces alterations in the early insulin signalling cascade nor changes the basal level of glucose uptake[ 57 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Thus, further exploration consisted of testing whether adrenergic receptors, which bind catecholamines, were involved in their stimulatory action on hexose uptake. Hence, diverse β-adrenoreceptor (β-AR) agonists have already been reported to modulate glucose transport activity in adipocytes, but with contradictory effects, from stimulatory[ 40 - 42 ] to inhibitory[ 31 , 43 ] depending on the nature (white, beige, brown) of the adipocytes, the animal species[ 44 ], and the experimental conditions tested.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that β-adrenoceptor stimulation increases expression, de novo synthesis, and translocation of these newly synthesized GLUT1 transporters to the plasma membrane, increasing glucose uptake [ 2 , 4 , 8 ]. To investigate whether glucose uptake as induced through Myo1c inhibition is regulated in a similar manner, quantitative PCR was performed to measure glucose transporter gene expression in brown and white adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The proliferation and maintenance of cells are constantly regulated so that the tissue will have appropriate capacity [ 27 ], and these morphological changes need to be rigorously regulated as over- or understimulation of this potent tissue under the wrong physiological conditions could have devasting implications on survival during birth and throughout life. Upon adrenergic exposure, BAT has been shown to consume, in addition to fatty acids, high amounts of glucose both in vitro and in vivo to the extent that it can affect body glucose clearance both acutely and chronically to support lipogenesis and thermogenesis [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ], with β-adrenergic stimulation increasing GLUT1 translation and translocation [ 8 ]. However, glucose uptake will not occur to the same extent under thermoneutral conditions when the need to combust additional fuel is unnecessary, although we [ 35 ] and others [ 39 ] have previously shown that β-adrenergic glucose uptake into brown adipocytes is a distinct and parallel pathway to non-shivering thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation